Links Between Perceptions of Successes, Problems and Health Outcomes Among Adult Chinese Children: The Mediating Role of Perceptions of Parents’ Feelings and Intergenerational Relationships - Yang, Jingjing; Zheng, Yong (Frontiers in Psychology, 2019)
Several studies have focused on adult children’s successes and problems and implications for their own well-being, but few studies have paid attention to their implications for adult children’s health outcomes. In the present study, we tested the links between perceptions of successes, problems, and their own health outcomes, as well as the mediating role of perceptions of parents’ feelings and intergenerational relationships. Adult children (n = 314; age 18–59) completed surveys on perceptions of successes (compared with counterparts, speculated how parents rate their successes, and compared with same-gender parent); problems (self’s, father’s, and mother’s); parents’ feelings (positive and negative); intergenerational relationships (intergenerational ambivalence and instrumental solidarity); and health outcomes [subjective well-being (SWB), psychological distress (PD), and self-rated health (SRH)]. Path analysis was conducted, a bootstrapped test was used. Results showed that perceptions of successes compared with counterparts were positively correlated with SWB and SRH; perceptions of successes compared with counterparts and perceptions of successes compared with same-gender parent were positively correlated with SWB and SRH via parents’ positive feelings; perceptions of successes that speculated how parents rate their successes and perceptions of successes compared with same-gender parent were negatively correlated with PD via parents’ negative feelings. Self’s problems were negatively correlated with SWB via direct ambivalence (DA), and were positively correlated with PD via parents’ negative feelings and DA, while mother’s problems were positively correlated with PD via parents’ negative feelings. There were no significant correlations between father’s problems and adult children’s health outcomes. This study underscores the importance of considering perceptions of parents’ feelings and DA in understanding the mechanisms of an individual’s mental health in family systems. This study sheds lights on considering an individual’s health in family systems and cultural contexts.